Efek penambahan enzim (amylase, protease, xylanase) dalam pakan terhadap berat telur dan diameter kuning telur pada itik campuran - Bagus Uda Palgunadi; Ratna Widyawati; Dian Ayu Kartika Sari; Halimah Tusadiah (VITEK : Bidang Kedokteran Hewan, 2021)
The purpose of this research aims to determine the effect of adding enzymes (amylase, protease, xylanase) in feed on egg weight and egg yolk diameter in mixed ducks. The experimental animals used were 24 laying ducks. The design used was a completely randomized design (CRD) with 4 treatments and 6 replications. The four treatments were P0 (Control), P1 (6 ducks with Avizym1502®5gram / kg), P2 (6 ducks with Avizym1502® 10gram / kg), and P3 (6 ducks given Avizym1502). ® 15gram / kg). This treatment is carried out once a day for 9 weeks. Before the treatment, the ducks were adapted for a week. After that, the initial egg weight and yolk diameter were measured at week 0, week 6, and week 9. Data obtained from the results of weighing eggs found an average value of P0 (59.1667 ± 3.9200a) g, P1 5gram / kg (56.1667 ± 2.9268a) g, P2 10gram / kg (60.1667 ± 4.9966a) g, and P3 15gram / kg (67.6667 ± 2.7325ᵇ) g. The results of data from examining the diameter of the egg yolk found an average value of P0 (45.03 ± 1.2956a) mm, P1 5gram / kg (44.35 ± 0.7969a) mm, P2 10gram / kg (45.75 ± 1.5694a) mm, and P3 15gram / kg (48.83 ± 0.7394ᵇ) mm. The data obtained were then analyzed using the ANOVA test which statistically showed that there was a significant difference (P <0.05) between egg weight and yolk diameter in mixed ducks treated with enzymes (amylase, protease, xylanase) in the feed.